2020
DOI: 10.1186/s12876-020-01323-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between transpancreatic sphincterotomy and needle-knife fistulotomy in difficulty biliary access, a retrospective study in Taiwan

Abstract: Background: Selective deep biliary cannulation is the first and the most important step before further biliary therapy. Transpancreatic sphincterotomy (TPS), and needle knife fistulotomy (NKF) were commonly used in patients with difficult cannulation, but few studies compare the outcome between TPS and NKF. Methods: A total of 78 patients who met the criteria of difficult cannulation in the National Taiwan University hospital from October 2015 to October 2017 were retrospectively reviewed. Their baseline demog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…We believe that the NKF method is safe in terms of perforation risk when performed by separating the structures above the bile duct layer by layer up to the sphincter muscle layer and by piercing the sphincter muscle by sight. 34 This safe profile is also supported by the absence of perforation with NKF cannulation in the 47-patient study of Liang et al 35 and the 34-patient study of Park et al 36 Moreover, Park et al 26 did not observe any perforation with NKF employment in 33 patients with perivaterian diverticulum, as in the 4 patients in the presented study. Furthermore, Lopes et al 9 observed a perforation in 1 of 72 patients with a common bile duct diameter ≤ 4 mm who underwent NKF cannulation.…”
Section: Discussionsupporting
confidence: 78%
“…We believe that the NKF method is safe in terms of perforation risk when performed by separating the structures above the bile duct layer by layer up to the sphincter muscle layer and by piercing the sphincter muscle by sight. 34 This safe profile is also supported by the absence of perforation with NKF cannulation in the 47-patient study of Liang et al 35 and the 34-patient study of Park et al 36 Moreover, Park et al 26 did not observe any perforation with NKF employment in 33 patients with perivaterian diverticulum, as in the 4 patients in the presented study. Furthermore, Lopes et al 9 observed a perforation in 1 of 72 patients with a common bile duct diameter ≤ 4 mm who underwent NKF cannulation.…”
Section: Discussionsupporting
confidence: 78%
“…The successful cannulation rate for TPBS with additional NKF was up to 83.9 %. The adverse events rates were not significantly different [7].…”
mentioning
confidence: 78%
“…Although some previous studies have compared NKP and TPS, the conclusions were inconsistent. However, several studies focused on this topic have been published recently [15, 16]. The aim of this meta-analysis was to compare NKP and TPS in difficult cannulation during ERCP.…”
Section: Introductionmentioning
confidence: 99%